Theoretical Aspects Of Medical Workers’ Criminal Liability - Spitsyna, Hanna; Davydenko, Ihor; Turska, Valeria (Archives of Criminology and Forensic Sciences, 2023)
The article considers theoretical foundations of criminal liability for medical professionals. The issue of legal liability has been studied. The lack of awareness among medical workers and their supervisors regarding legal liability set by current legislation for violations in healthcare has been stressed. In particular, criminal liability is singled out as the most severe kind of legal liability. The main focus is on professional medical crime, its features and components. Crimes committed intentionally or negligently are described separately. An analysis of the proposal to refine the Criminal Code of Ukraine has been carried out, in particular with regard to the possibility of supplementing the law with a separate section devoted to crimes committed by medical professionals. The Article Aim is to study theoretical foundations of criminal liability for medical professionals through the systems analysis of legal regulation. The research paper provides a comprehensive overview of legal liability, with a specific focus on criminal liability for medical practitioners. The methods of structural analysis and synthesis have been used to divide obtained information into distinct structural units and to systematically merge various aspects of information into a single structured presentation system aimed at summarizing information regarding criminal liability of medical professionals for crimes committed while performing their professional duties. Conclusions. The findings suggest that there is a need for cooperation among the scientific community, legislative bodies, and medical professionals with the aim of developing legal norms and criminal liability system that will ensure protection of patients’ rights and promote ethical and safe execution of medical duties.